Dieting Patterns With Hypertension In Menopause 56-60 Years Old (At Ponkesdes Sugihwaras, Jenu District, Tuban Regency) - Dyah Pitaloka; Tiara Putri Ryandini; Mariyatul Qiftiyah (Jurnal MIDPRO, 2021)
Non-communicable diseases (PTM) are the leading cause of death globally with the highest rates of cardiovascular disease with one of them being an increase in blood pressure or what is commonly called hypertension (Kurniingtyas B. F, et al, 2016). 32 cases of hypertension were experienced in menopausal women aged 56-60 years as many as 59% of the incidence. The purpose of this study was to find out the relationship between eating patterns and the incidence of hypertension in menopausal women aged 56-60 years (in Ponkesdes Sugihwaras, Jenu subdistrict, Tuban regency). The study design was non-experimental with a correlational approach, the population used in this study were all 56-60-year-old Menopause Women (in Ponkesdes Sugihwaras, Jenu District, Tuban Regency). with a large sample of research 30 respondents who were determined using systematic random sampling techniques. The independent variable in this study is diet, while the dependent variable is blood pressure. The instruments used in data collection are SOPs and Observation sheets. Analysis of the study used the coefficient test phie significance of the Asymp value. Sig. (2-sided) (α) = <0.05. Based on the results of the statistical test research the Asymp value was obtained. Sig. (2-sided) (α) = 0.003 (α <0.05). Statistical test results show that dietary variables affect blood pressure.